The Ultrastructural Analyses of Meniscus Histology in Osteoarthritic Knees - Alper Kaya; Sibel Serin Kılıçoğlu; Berk Güçlü; Esra Erdemli; İsmet Teoman Benli (Archives of Rheumatology, 2009)
Objective: Menisci are fibrocartilage tissue that have many functions in the knee joint. Studies showed the early progression of osteoarthrtic changes after meniscectomy. The osteoarthritic knee has some meniscal changes associated with articular cartilage degeneration. This study aimed to investigate the ultrastructural meniscal changes in degenerated knee joints. Materials and Methods: Samples were excised from patients who underwent total knee arthroplasty for primary varus osteoarthritis of the knee joint. Twenty medial menisci were examined histologically by light microscopy and transmission electron microscopy and compared with two normal menisci samples. Results: Ultrastructure of the tissue specimens taken from the pathologic meniscus group demonstrated a heterogeneous course in the collagen fibers. It was composed of concentric lamellae of fibrous bundles that were disorganized in some areas. Moreover, the amount of collagen fibers was decreased qualitatively in these groups. While metachromasia was remarkable around nearly all of the chondrocytes in the control group, it was detected especially in the matrix of the cell proliferation region in the degenerated meniscus group. Chondrocytes were oval and elongated cells in the degenerated menisci. The territorial matrix was mostly sparse or absent in the degenerated menisci; however, there were also instances where a typical chondrocyte was surrounded by territorial matrix containing proteoglycan particles and fibrils. Intracytoplasmic small lipid droplets in the chondrocytes of normal meniscus were also present but they were of more frequent occurrence and more prominent in size in the degenerated meniscus group. Electron dense gigantic calcified bodies in the intercellular matrix were also seen in the degenerated menisci specimens. One of the important findings of the study is the decreased synthesis of glycosaminoglycan in the degenerated menisci. Conclusion: This study shows the secondary structural changes of the meniscus in the osteoarthritic knee joint. (Turk J Rheumatol 2009; 24: 118-22)